2016
DOI: 10.1007/s11661-016-3545-0
|View full text |Cite
|
Sign up to set email alerts
|

Designing the Color of Hot-Dip Galvanized Steel Sheet Through Destructive Light Interference Using a Zn-Ti Liquid Metallic Bath

Abstract: The color of hot-dip galvanized steel sheet was adjusted in a reproducible way using a liquid Zn-Ti metallic bath, air atmosphere, and controlling the bath temperature as the only experi mental parame ter. Coloring was found only for sample s cooled in air and dipped into Ti-containing liquid Zn. For samples dipped into a 0.15 wt pct Ti-containing Zn bath, the color remained metallic (gray) below a 792 K (519°C) bath temperature; it was yellow at 814 K ± 22 K (541°C ± 22°C), violet at 847 K ± 10 K (574°C ± 10°… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…It is worth to mention that the Cu crystals on top of the NML seem natural metallic in light microscope, confirming the oxide layer is not too thick on them. Although oxide films might change the visible color of metals [47], but only above a critical thickness [48]. Using Eq.…”
Section: Microstructural Evolution During Heattreatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to mention that the Cu crystals on top of the NML seem natural metallic in light microscope, confirming the oxide layer is not too thick on them. Although oxide films might change the visible color of metals [47], but only above a critical thickness [48]. Using Eq.…”
Section: Microstructural Evolution During Heattreatmentmentioning
confidence: 99%
“…Using Eq. (10a) of [48] the smallest thickness of the copper oxide layer of 37 nm is found that ensures the minimum of 400 nm wavelength of destructive interference if the refractive index of the CuO/Cu 2 O taken as 2.7 ± 0.1 (see p. 236 of [44]), where 400 nm is the lowest wavelength of light visible by humans. This means the thickness of the oxide layer on the micron-sized Cu-crystals is surely below 37 nm, which is less than 2 % of the total size of the Cucrystals, explaining why the presence of oxygen on Cu crystals seems negligible in Figs 7,8.…”
Section: Microstructural Evolution During Heattreatmentmentioning
confidence: 99%
“…Fémek korrózióvédõ bevonatainak kialakításakor esztétikai szempontok is szerepet játszanak 17,18 . Ezért van jelentõsége átlátszó bevonatok fejlesztésének, melyek nem fedik el a bevonandó fém színét, vagy éppen elõnyösen módosítják azt 12…”
Section: Transzparens Korrózióvédõ Bevonatok Kialakítása Cinkhordozónunclassified
“…NANO-MATERIALS play an increasing scientific and social role. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In the past, nano-materials were simplified to single nano-particles. However, it has been clear for some decades that the real use of nanomaterials is expected if they form macroscopic articles with nano-structure inside.…”
Section: Introductionmentioning
confidence: 99%